2012
DOI: 10.1159/000343699
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock Wave Therapy Combined with Vascular Endothelial Growth Factor-C Hydrogel for Lymphangiogenesis

Abstract: Background/Aims: Lymphedema is a clinically incurable disease that occurs commonly after lymph node dissection and/or irradiation. Several studies have recently demonstrated that extracorporeal shock wave therapy (ESWT) could promote lymphangiogenesis associated with expression of vascular endothelial growth factor (VEGF)-C. This research concerned primarily the synergistic effect of ESWT combined with VEGF-C incorporated hydrogel (VEGF-C hydrogel) combination therapy for promoting lymphangiogenesis and ultima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Previous work has shown that various forms of VEGF-C delivered from gelatin [41, 42] and albumin alginate [6] promoted lymphangiogenesis in vivo . However, the use of injectable and degradable binary alginate hydrogels to deliver bioactive and temporally controlled VEGF-C and VEGF-D has not been specifically tested yet.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that various forms of VEGF-C delivered from gelatin [41, 42] and albumin alginate [6] promoted lymphangiogenesis in vivo . However, the use of injectable and degradable binary alginate hydrogels to deliver bioactive and temporally controlled VEGF-C and VEGF-D has not been specifically tested yet.…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate, ATP triggered ERK1/2 pathway activation improves cell proliferation and wound healing [32,33], and modulation of the inflammatory process via TLR3 [34] and other molecular signals [35,36] seem to accelerate wound healing. Biological responses induced by ESWT include angio-and lymphogenesis [36][37][38][39][40][41][42][43]; recruitment, proliferation and differentiation of endogenous stem cells [42,[44][45][46][47]; osteogenesis [48][49][50][51][52][53]. All of these are essentially involved in the initiation of the healing response, thus implicating ESWT as a highly effective modality due to its multisided target systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a significant reduction of lymphedema was reported clinically following four ESWT sessions in females with secondary lymphedema following breast cancer treatment [6]. In animal experiments ESWT and the vascular endothelial growth factor (VEGF-C) hydrogel appear to exert a synergistic effect in promoting lymphangiogenesis [22]. …”
Section: Discussionmentioning
confidence: 99%